Penetapan Kuasa Asuh Terhadap Anak di Bawah Umur Pasca Perceraian: Analisis Putusan Pengadilan Agama Lubuk Pakam Nomor 0197/Pdt.G/2021/PA.Lpk - Amin, Muhammad Habibul; Harahap, Mhd. Yadi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This article aims to investigate how the process of determining custody of children who have not yet reached the age of majority or who are not mumayyiz after divorce is in accordance with Indonesian laws and regulations, as well as how the law is applied in handling disputes related to this issue. This article applies a normative juridical research approach as an analytical tool to examine and interpret legal data contained in legislation, especially Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law and Presidential Instruction No. 1 of 1991. The results of the article show that firstly, although the Law on Marriage does not specifically regulate the process of determining custody of children under the custody of children who have not reached the age of majority after divorce, this issue is regulated in detail in Article 105 and Article 156 Compilation of Islamic Law. Determination of child custody is based on considerations of morality, health, and the parents' ability to educate children, which aims to ensure the child's primary interests. Second, law enforcement in resolving disputes related to determining child custody is still not fully in line with current needs, so it is necessary to revise Law Number 1 of 1974 concerning Marriage and KHI to better meet current demands. The judge's considerations in determining custody are not only based on formal legal aspects of written legal rules, but can also be based on moral considerations, social values, including paying attention to environmental conditions, exploring the track records of both parents and the psychology of the children in the family at that time.